Effects of the mobile gates (MOSE) closure on the ecosystem functioning of the Venice lagoon: an experimental assessment with enclosures - Cibic, Tamara; Baldassarre, Laura; Auriemma, Rocco; Balestra, Cecilia; Banchi, Elisa; Battaggia, Greta; Bazzaro, Matteo; Cerino, Federica; De Pascale, Fabio; Diociaiuti, Tommaso; Guarneri, Irene; Kralj, Martina; et al. (Frontiers in Marine Science, 2025)
The MOSE (Experimental Electromechanical Module), consisting of rows of mobile gates can temporarily isolate the Venice lagoon from the Adriatic Sea during extreme high tides. To investigate how the lagoon ecosystem is affected by a prolonged segregation from the oxygenating seawater, we performed two enclosure experiments in July 2019 (48h) and October 2020 (28h) by artificially secluding small portions of the organic-enriched Palude di Cona area, using 18 mesocosms ( 0.8 m3 each). We followed the closure effects on planktonic and benthic communities at several trophic levels (i.e. prokaryotes, microalgae, consumers). Our results suggest that the reduced hydrodynamics induced by the MOSE closure, leading to an enhanced deposition of the suspended material over time, affects the main biological processes and the pelagic-benthic coupling in the Venice lagoon. Over the summer experiment, the concentrations of N-NO3 and N-NO2, and some phototrophic components and functions (i.e. chl-a, Synechococcus, picoeukaryotes, primary production) in the water column were significantly reduced. The smallest phototrophs gradually settled towards the sediments, drastically diminishing their abundance, whereas the largest phytoplankton cells (dinoflagellates and diatoms) took advantage and increased their density during the experiment due to the significantly higher availability of N-NH4, deriving from the prompt degradation of organic matter. The higher Total Organic C content in surface sediments, deriving from the gradual sinking of suspended particulate organic matter, stimulated the microbial components and processes notably, both in the water column and in the sediments. In parallel, the higher availability of N-NH4 stimulated the microphytobenthic abundance and benthic primary production. In the autumn experiment, most of the investigated variables displayed opposite patterns, likely ascribable to the different season and diverse meteorological conditions. Our holistic approach represents a reference to evaluate the impact of floodgates on coastal ecosystems, an increasingly frequent engineering solution around the world to rising sea levels.